2020
DOI: 10.1002/jhrm.21450
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of medical malpractice claims involving emergency medicine physicians

Abstract: Background: Identifying characteristics of malpractice claims involving emergency medicine (EM) physicians allows leaders to develop patient safety initiatives to prevent future harm events. Methods: A retrospective study was performed of paid/unpaid claims closed 2007 to 2016 from Comparative Benchmarking System. Claims were identified by physician specialty involved (EM, internal medicine, general surgery). Various characteristics were compared by physician specialty. Multivariable regression was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…However, this ED CT utilization is similar compared to like institutions, including only adult EDs (32/100), those with 80 k–100 k annual ED visits (32/100), and level 1 or 2 trauma centers (31/100) [ 21 ]. Additionally, the local medicolegal environment in Illinois as well as concerns regarding diagnostic accuracy likely contribute to increased ED diagnostic test utilization [ 44 , 45 ]. An additional limitation is that our analysis focuses on presentation to the ED and is not able to capture those patients who may have been evaluated in the outpatient setting by primary care or other providers as well as may have sought evaluation in private outpatient only radiology centers, both of which could have provided a perception of safer, less risky care.…”
Section: Discussionmentioning
confidence: 99%
“…However, this ED CT utilization is similar compared to like institutions, including only adult EDs (32/100), those with 80 k–100 k annual ED visits (32/100), and level 1 or 2 trauma centers (31/100) [ 21 ]. Additionally, the local medicolegal environment in Illinois as well as concerns regarding diagnostic accuracy likely contribute to increased ED diagnostic test utilization [ 44 , 45 ]. An additional limitation is that our analysis focuses on presentation to the ED and is not able to capture those patients who may have been evaluated in the outpatient setting by primary care or other providers as well as may have sought evaluation in private outpatient only radiology centers, both of which could have provided a perception of safer, less risky care.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that the judgment for the plaintiff rate was 13.3% in the ED setting for medical malpractice in Taiwan 21 and 31% in 2020 in the US. 11 Diagnostic errors were involved in 35–37% of the medical lawsuits in the ED in the US. 22 , 23 This is considerably lower than the rate in Japan (68.5%).…”
Section: Discussionmentioning
confidence: 99%
“… 20 According to three studies of US medical lawsuits, the most common final diagnoses related to diagnostic errors in the ED are acute myocardial infarction, appendicitis, pulmonary embolism, and fractures. 11 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer weiteren Umfrage benennen Notfallmediziner als Hauptgrund die Angst, eine Diagnose mit geringer Wahrscheinlichkeit zu verpassen (69%) und die Sorge vor möglichen Rechtsstreitigkeiten (64%; [31]). Eine retrospektive Kohortenstudie von Arzthaftungsansprüchen von Notfallmedizinern aus den USA berichtet, dass mehr als die Hälfte der Verfahren sich aus möglichen Fehlern von diagnostischen Prozeduren ableitet [32]. Obwohl das juristische Vorgehen in den USA sicherlich nicht auf die mitteleuropäische Situation übertragbar ist, geben diese Untersuchungen einen interessanten Einblick.…”
Section: Individuelle Vorgehensweisen Beeinflussen Diagnostische Maßn...unclassified